Learning styles of music students and preference to study with or without music / Hawa Nor Adilah Md Yusofe - Md Yusofe, Hawa Nor Adilah (Faculty of Music, 2015)
The purpose of this project was to investigate the learning styles of music students and their preference to study with or without music. Specifically, this study looked at two elements: students preferred learning style and music listening preference during study. The sample comprised of 100 students from three programs at the Faculty of Music, UiTM which is Music Education (MU220), Music Composition (MU221 and Music Performance (MU222). Independent variables such as gender, program and years of study were used to compare descriptive statistics between sections and item in each section. Data on learning styles were analyzed through Fleming's scoring chart and descriptive statistics employing independent t-test were used to compare between gender and student's preference to study with or without music background. Results of the study found that, 55% had single learning style and 45% had multimodal learning style. Among multimodal learners, bi-modal learners comprised of 67%, tri-modal learners were 24%, and quad-modal learners were 9%. The most preferred combination of learning style among bi-modal learners were Auditory- Kinesthetic (AK) 36% (male, n = 7, female, n = 9). Female students had more diverse learning style preferences with several ARK and VARK combinations. A percentage of students preferring to study with music background is 73% (male, n = 37, female, n =36) and without music background is 27% (male, n = 13, female, n = 14). There are no differences between gender and student's preference to study with and without music. Most students in this study preferred single learning style inputs in their learning process. Furthermore, female students preferred used several combinations of ARK and VARK learning styles. The results of student's preference to study with or without music revealed that those music degree students preferred to study with music background.